A Study on Challenges and Growth of Medical Tourism In India: Challenges and Opportunities in India's Medical Tourism Industry (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Medicaltourism is becoming a popular option for tourists across the globe. Itencompasses primarily and predominantly biomedical procedures, combined withtravel and tourism. The term medical tourism has been coined by travel agenciesand the mass media to describe the rapidly growing practice of travellingacross international borders to obtain hi-tech medical care. Various countrieslike Thailand, Malaysia, India, etc are promoting medical tourism aggressively. Thekey competitive advantages of India in medical tourism stem from the following:low cost advantage, strong reputation in the advanced healthcare segment(cardiovascular surgery, organ transplants, eye surgery etc.) and the diversityof tourist destinations available in the country. The key concerns facing the industryinclude: absence of government initiative, lack of a coordinated effort topromote the industry, no accreditation mechanism for hospitals and the lack ofuniform pricing policies and standards across hospitals.  Medical tourism or health care tourism is fastgrowing multibillion-dollar industry around the world. It is an economicactivity that entails trade in services and represents the mixing of two of thelargest world industries: medicine and tourism. The paper identifies thestrengths of India’s medical tourism service providers and points at a numberof problems that may reduce the growth opportunity of this industry. Thispaper focuses on the key issues and opportunities possessed by Indian medicaltourism sector that enable it to overcome domestic and international barrierson upgrading its medical services. Finally, this paper analyses and concludesthe main reasons why the developing country like India attracts foreigntourists for the medical treatment.